2005
DOI: 10.1080/08035250410023331
|View full text |Cite
|
Sign up to set email alerts
|

Leisure activities in adolescents with headache

Abstract: This study provides additional data on the activity status and headache complaints in adolescents. The results indicate that frequent computer use is associated with both tension-type headache and migraine, and intensive overall sports activities are characteristic of adolescents with migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Most of them found adverse associations for frequent use of computers and both migraine and TTH [27-30]; only the study by Smith et al did not find a statistically significant effect [31]. In a recent review on health complaints due to mobile phone use [15] results were controversial: While two studies found a statistically significant association between exposure to mobile phones and headache [[22,23]; see also [5,24]], two other studies did not [25,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of them found adverse associations for frequent use of computers and both migraine and TTH [27-30]; only the study by Smith et al did not find a statistically significant effect [31]. In a recent review on health complaints due to mobile phone use [15] results were controversial: While two studies found a statistically significant association between exposure to mobile phones and headache [[22,23]; see also [5,24]], two other studies did not [25,41].…”
Section: Discussionmentioning
confidence: 99%
“…Controversial results were observed: While some observational studies reported statistically significant associations between the self-reported duration of mobile-phone calls per day or exposure to mobile-phone base stations and headache [5,22-24], experimental studies with controlled exposure duration to radio frequency fields did not find significantly increased headache [25,26]. Regarding the use of computers , most studies on adolescents found statistically significant increased prevalences of migraine and TTH [27-30]; only one recent study by Smith et al did not find such an association [31]. Other studies showed harmful associations between frequent watching of television and headache [32], especially migraine [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…A low level of Physical Activities (Phys‐Act) potentially combined with too much Electronic Media Utilization such as TV watching, etc (TV) is commonly expected to be a risk factor for headache in general 27 . The associations have been found to be inconsistent and even contradictory for various pain syndromes, however, 27‐32 so further examination was needed. We also assessed the amount of Free Time for Leisure Activities (not pre‐regulated or planned; Leisure) mainly because our clinical impression of children in treatment for headache indicated that spending little or no time on self‐regulated activities could be a risk factor 7 .…”
Section: Domain Of Behavioral Factorsmentioning
confidence: 99%
“…headache [3,4], neck-shoulder pain [3,5] and low back pain [5-7], which have been observed as more common among computer users than among non-users. A dose-response relationship between computer use time and the occurrence of symptoms has been noted in a previous study [5].…”
Section: Introductionmentioning
confidence: 99%